HUBUNGAN ANTARA ORGANIZATIONAL CIIZEN BEHAVIOR (OCB) DAN MASA KERJA DENGAN KINERJA GURU SEKOLAH DASAR NEGERI PASCA PROGRAM SERTIFIKASI GURU - ITA RACHMAWATI (Universitas Negeri Surabaya, 2013)
Abstrak Penelitian ini bertujuan untuk menguji apakah ada hubungan antara organizational citizen behavior (OCB) dan masa kerja dengan kinerja. Subjek penelitian ini adalah 85 Guru Sekolah Dasar Negeri di kecamatan Taman. Pengumpulan data menggunakan kuesioner untuk mengungkap hubungan antar variabel. Teknik analisis data dalam penelitian ini adalah teknik korelasi ganda. Hasil korelasi antara organizational citizen behavior (OCB) dengan kinerja adalah sebesar 0.765 dengan p = 0.000 (p<0.05), artinya terdapat hubungan yang signifikan antara organizational citizen behavior (OCB) dengan kinerja. Hasil korelasi antara masa kerja dengan kinerja adalah sebesar -0.072 dengan p = 0.512 (p>0.05), artinya tidak terdapat hubungan yang signifikan antara masa kerja dengan kinerja. Kata Kunci: Organizational Citizen Behavior (OCB), Masa Kerja, Kinerja, Guru. Abstract The main purpose of this research is to test whether there is a correlation between Organizational Citizen Behavior (OCB) and length of service with performance. Subject of this research are 85 teachers who are teaching at Taman Sub-District state elementary school. Data collected by questionnaires to uncover the relation between variables. Data analytical technique used in this research is multiple correlations. The result of correlation between Organizational Citizen Behavior (OCB) with performance is 0.765 on significant level of p = 0.000 (p < 0.05), showed that there is a significant correlation between Organizational Citizen Behavior (OCB) with performance. The result of correlation between length of service with performance is -0.072 on significant level of p = 0.512 (p > 0.05), showed that there is no correlation and insignificant between length of service with performance. Key words: Organizational Citizen Behavior (OCB), Length of Service, Performance, Teacher.